PENGARUH KEPUASAN KERJA DENGAN MOTIVASI TERHADAP KINERJA ANGGOTA POLSEK TEGOWANU, KAB GROBOGAN - Siti Kholifah; Maya Utami Dewi (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2022)
In an effort to realize the Polsek's mission, the author would like to pay attention to one of the visions of the Polsek mentioned above, namely "Managing Polsek human resources professionally in achieving Polsek goals, namely the realization of domestic security so that it can encourage increased enthusiasm for work in order to achieve community welfare". Quality human resources are crucial for Polsek in realizing its mission. It is undeniable that Polsek HR still needs a lot of improvement, among others, in serving the community according to the main duties and functions of Polsek members. After the Polsek made up its mind to continue to improve itself, along the way, there were still disciplinary actions and violations of the law by unscrupulous members of the Polsek. Many of the violations committed by members of the Tegowanu Police, Grobogan Regency, included leaving their duties without notice, being involved in criminal acts such as drug abuse which resulted in delays in promotion to PTDH (Disrespectful Dismissal). This is the current internal task of the Polsek, considering that this problem is not easy to be eliminated by the leaders of the Polsek.